Yonathan Alfonso Situmorang, Darma Bakti*, Hasanuddin - Yonathan Alfonso Situmorang; Darma Bakti; Hasanudin Hasanuddin (Jurnal Agroekoteknologi, 2015)
Metarhizium able to control variable growth phase of insect, such as egg, larvae, pupae, and adult.Effect of fungicide on Metarhizium is rarely reported. This research aims to determine impact offungicide to fungal colony growth of Metarhizium anisopliae (Metch) Sorokin. Conducted at PlantPathology Laboratory, Agriculture Faculty, University of North Sumatera, from August untilNovember 2013. Arranged non-factorial completely randomized design with twenty one treatmentsand three replications. Petridish contained 1 ml fungicide + 9 ml PDA, used one point technic,incubated at room temperature. The result showed that fungicide effect toward fungal colonygrowth of Metarhizium anisopliae (Metch) Sorokin. Highest fungal colony diameter was on 1.000ppm Mankozeb 80 WP which reached 7.67 cm, meanwhile lowest fungal colony diameter was on20.000 ppm Tebukonazol 25 WP which reached 0.88 cm. Highest fungal colony extensive was on1.000 ppm Mankozeb 80 WP which reached 45.23 cm2, meanwhile the lowest fungal colonyextensive was on 20.000 ppm Tebukonazol 25 WP which reached 0.53 cm2.Keywords : Metarhizium anisopliae, fungicide, biological agent.